Post-graduate Teachers’ STEM Education Experiences and the Development of their 21st Century Skills: A Case Study of Two Higher Education Institutions in South Africa and Mauritius - Ronicka Mudaly; Bongani P. Ndlovu; Tamirirofa Chirikure; Doras Sibanda; Merventharan Perumal Moodley; Fawzia Bibi Narod; Vickren Narrainsawmy (E-Journal of Humanities, Arts and Social Sciences)
Developing strong 21st century skills is crucial for teachers, and exploring how Science, Technology, Engineering, and Mathematics (STEM) education experiences can contribute to this development in teacher education holds significant value. The purpose of this research was to explore how STEM education experiences foster the development of 21st century skills in post-graduate teachers within the context of the Global South. Methodologically, it followed an exploratory case study with a sample of 53 postgraduate students who were purposively selected from one university in South Africa and one higher education institution in Mauritius. The first set of data was generated using a semi-structured questionnaire. To corroborate the questionnaire data, a sample of 5 postgraduate teachers was interviewed, forming the second data set. Findings from this study revealed that the “ways of thinking” were the 21st century skills that were most enhanced by the STEM experience. This is compared with other 21st century skills sets like living in the world, ways of working, and tools for working, which were developed to a lesser extent. Data from the interviews confirmed that postgraduate teachers find the ways of thinking, due to their experiences with STEM, to be the most enhanced 21st century skill. The findings in this paper have implications for teacher development, especially in STEM education. It recommends that teacher education programs in the Global South leverage the potential of STEM education experiences to equip teachers with the necessary 21st century skills for effectively preparing future generations for the challenges and opportunities they will encounter.